Effects of two combined oral contraceptives containing ethinyl estradiol 30 mu g combined with either gestodene or drospirenone on hemostatic parameters, lipid profiles and blood pressure - YILDIZHAN, BEGÜM (SPRINGER HEIDELBERG, 2009)
The aim of this study is to compare the effect of ethinyl estradiol 0.03 mg/gestodene 0.075 mg (EE/GSD) with ethinylestradiol 0.03 mg/drospirenone 3 mg (EE/DRSP) administered according to conventional 21/7 regimen on body mass index (BMI), blood pressure (BP), lipid metabolism and hemostatic parameters. In this study, 160 healthy women were randomized to EE/GSD mg or EE/DRSP for 12 months. Mean differences in BMI, high density lipoprotein-cholesterol (HDL-C) and low density lipoprotein-cholesterol (LDL-C), total cholesterol (TC) levels and BP compared to baseline were assessed. One hundred and forty-five (89%) of the women completed all 12 treatment cycles. The subjects randomly assigned into two treatment groups. Group EE/GSD (n = 71) and group EE/DRSP (n = 72). In group B, BMI values were significantly lower than baseline at the sixth cycle. DRSP/EE had more favorable effects on BP than GSD/EE with the mean systolic and diastolic BPs remaining lower in the DRSP/EE group. The difference between the two preparations was not statistically significant at the end of the study. TC levels remained similar in both groups throughout the study period. In both groups LDL-C levels decreased, triglyceride and HDL-C levels significantly increased from baseline levels. These changes result in increasing HDL-C/LDL-C ratio, demonstrating anti-atherogenic effect. Menstrual cycle patterns and the incidence of adverse events were similar between groups. The duration of withdrawal bleeding decreased during the study for both groups and was similar. The EE/DRSP regimen provides good cycle control with reliable contraceptive efficacy and low incidence of adverse events. Compared with the EE/GSD preparation, the EE/DRSP preparation demonstrated a more favorable effect on BMI and BP with the mean BMI and mean BP remaining lower than baseline mean. The new formulation may be especially beneficial for women susceptible to body weight gain and rise in BP.
Keywords: Oral contraceptives; Ethinylestradiol; Drospirenone; Gestodene; RENIN-ALDOSTERONE SYSTEM; CYCLE CONTROL; CARBOHYDRATE-METABOLISM; PROGESTIN DROSPIRENONE; OPEN-LABEL; DESOGESTREL; ETHINYLESTRADIOL; EFFICACY; LIPOPROTEIN; TOLERANCE